Further characterization of clinical and laboratory features in VEXAS syndrome: large‐scale analysis of a multicentre case series of 116 French patients. (28th November 2021) - Georgin‐Lavialle, S.; Terrier, B.; Guedon, A.F.; Heiblig, M.; Comont, T.; Lazaro, E.; Lacombe, V.; Terriou, L.; Ardois, S.; Bouaziz, J.‐D.; Mathian, A.; Le Guenno, G.; et al.
Summary: Background: A new autoinflammatory syndrome related to somatic mutations of UBA1 was recently described and called VEXAS syndrome ('Vacuoles, E1 Enzyme, X‐linked, Autoinflammatory, Somatic syndrome'). Objectives: To describe clinical characteristics, laboratory findings and outcomes of VEXAS syndrome. Methods: One hundred and sixteen patients with VEXAS syndrome were referred to a French multicentre registry between November 2020 and May 2021. The frequency and median of parameters and vital status, from diagnosis to the end of the follow‐up, were recorded. Results: The main clinical features of VEXAS syndrome were found to be skin lesions (83%), noninfectious fever (64%), weight loss (62%), lung involvement (50%), ocular symptoms (39%), relapsing chondritis (36%), venous thrombosis (35%), lymph nodes (34%) and arthralgia (27%). Haematological disease was present in 58 cases (50%): myelodysplastic syndrome (MDS; n  = 58) and monoclonal gammopathy of unknown significance ( n  = 12; all patients with MGUS also have a MDS). UBA1 mutations included p.M41T (45%), p.M41V (30%), p.M41L (18%) and splice mutations (7%). After a median follow‐up of 3 years, 18 patients died (15·5%; nine of infection and three due to MDS progression). Unsupervised analysis identified three clusters: cluster 1 (47%; mild‐to‐moderate disease); cluster 2 (16%; underlying MDS and higher mortality rates); and cluster 3 (37%; constitutional manifestations, higher C‐reactive protein levels and less frequent chondritis). The 5‐year probability of survival was 84·2% in cluster 1, 50·5% in cluster 2 and 89·6% in cluster 3. The UBA1 p.Met41Leu mutation was associated with a better prognosis. Conclusions: VEXAS syndrome has a large spectrum of organ manifestations and shows different clinical and prognostic profiles. It also raises a potential impact of the identified UBA1 mutation. Abstract : What is already known about this topic? VEXAS syndrome is a recently described autoinflammatory disease related to UBA1 mutation. The clinical phenotype includes patients with thrombosis, fever, chondritis, neutrophilic dermatosis and MDS. What does this study add? The main clinical features of VEXAS patients remain recurrent fever (64.7% vs. 72%, in original description by Beck et al .), skin lesions (83.6% vs. 88%), lung infiltrates (49.1% vs. 72%), unprovoked thrombosis (35.5% vs. 44%), with new features such as arthralgia (28.4%), ocular involvement (40.5%) or lymph node enlargement (34.5%), expanding the previous clinical phenotype of VEXAS syndrome. We identified 3 clusters of VEXAS syndrome, including an MDS‐related phenotype; mild‐to‐moderate disease with less fever, chondritis and thromboembolism, and one with more 'inflammatory' profile characterized by cutaneous vasculitis lesions and relapsing profile. A phenotype–genotype association was observed for UBA1 p.Met41Leu which was associated with less 'inflammatory' and mild‐to‐moderate phenotype and better overall prognosis. Linked Comment:  L.T. Nicholson and L.M. Madigan. Br J Dermatol 2022; 186 :392–393 . Plain language summary available online